A case study of family-owned newspapers adapting and surviving in two rural states - Powers, Angela M.; Sohn, Ardyth Broadrick (My University, 2013)
Organizational ecologists follow the life histories of organizational populations, studying events such as founding, disbanding, and mergers. Newspaper organizations, for example, are often far from rational in their decision making to start, operate and end business practices. For this study, two daily papers located in rural states are analyzed within the context of organizational ecology, which has evolved from the physical sciences. For the larger market, rural-state newspaper, managers took an instrumental approach of quickly adapting new trends and technology. Because of economic uncertainties, a dismantling of such variations occurred. For the smaller market, rural-state newspaper, an institutional approach was most prevalent. Strong family ties and an assortment of family business ventures such as the streaming of high school sports supported the ability of this newspaper to continue business as usual throughout the timeframe of the study. Avoiding risk resulted in a stronger financial situation. This study indicates ecological analysis of newspapers is an attractive research method when organizations are subject to strong inertial pressures and face changeable, uncertain futures, as is the case in newspapers today.
Keywords: Newspapers; Organizational ecology; Competition; Survival